Left Atrial Size Contribution to the Predictive Capacity of Two Scores for Atrial Fibrillation in the Postoperative Period of Cardiac Surgeries - Silva,Natália Aline da (2019)
Abstract Background: Postoperative atrial fibrillation (POAF) is a common complication associated with undesirable outcomes; hence, the provision of appropriate tools is important to help identify patients at risk. Objectives: To evaluate the predictive capacity of the CHADS2 and CHA2DS2-VASc scores, alone and combined with left atrial (LA) size, for the onset of POAF in patients undergoing coronary artery bypass grafting and/or valvular surgery. Methods: We performed a retrospective cohort study on 144 patients. A decision tree was used to identify the cut-off values of the CHADS2 and CHA2DS2-VASc scores and LA size in order to calculate sensitivity, specificity, predictive-value positive (PVP), and predictive-value negative (PVN), in addition to regression models. The receiver operating characteristic (ROC) curve was used to estimate the accuracy of the models. The level of significance adopted was 5%. Results: Patients who developed POAF were older (p = 0.050), had reduced left ventricular ejection fraction (p = 0.045), longer hospital length of stay (p = 0,018), but their mean CHADS2 (p = 0.077) and CHA2DS2-VASc (p = 0.109) scores were similar to those of patients with no arrhythmia. LA size improved the predictive capacity of the CHADS2 score, in terms of specificity and PVP, and of the CHA2DS2-VASc score, in terms of sensitivity and PVN. However, the CHADS2 (OR = 1.198; CI95% = 0.859-1.156) and CHA2DS2-VASc (OR = 1.047; CI95% = 0.784-1.401) scores were not predictors of POAF, either alone or in combination with LA size (OR = 1.163; CI95% = 0.829-1.648 and OR = 1.065; CI95% = 0.795-1.433). Conclusion: The CHADS2 and CHA2DS2-VASc scores alone or in combination with LA size did not show good predictive capacity for POAF.